Laboratory manual applied mechanics / Nor Fazli Abdull Manan, Nik Rozlin Nik Mohd Masdek and Abdul Hakim Abdullah - Abdull Manan, Nor Fazli; Nik Mohd Masdek, Nik Rozlin; Abdullah, Abdul Hakim (UiTM Press, 2023)
Applied Mechanics Lab (MEC424) consists of three types of laboratory (Material Science, Dynamics and Strength of Material) that provides students with the opportunity to apply knowledge in mechanics and adapting to the Mechanical Engineering Programme. Each class of student will be divided into three (3) groups and parallel sessions will be carried out for each lab for four (4) weeks each and rotations will be done to complete all three courses of experiments. The team is formed by the course Resource Person (RP) to ensure smooth running for the course. All information and announcements for MEC424 is displayed on the notice board in each lab.